EXAMINING THE MEANING OF GEN ALPHA SLANG: A PRAGMATIC REVIEW OF SOCIAL MEDIA DISCOURSE - Mazaya, Aurora (Bahasa Indonesia Prima, 2025)
The use of Gen Alpha slang on social media is feared to have an impact on formal contexts. As a result, previous generations may not understand the meaning of these slang expressions. As a consequence, the use of good and correct Indonesian language in formal contexts may be neglected. This research aims to analyze the meaning and purpose behind the use of Gen Alpha slang words on social media, and to increase the understanding of the meaning of Gen Alpha slang in social media interaction and communication. The research data was collected from social media platforms such as Instagram, X, and TikTok. The method used is content analysis with a qualitative approach. The research object is Gen Alpha slang words, while the subject is social media users who use these slang words in comments or posts. Of the 15 purposes of using slang that has been identified, 6 dominant purposes were found in this research, with sarcasm being the most common purpose. The use of slang out of context can be a source of miscommunication and misperception among users.